Toward Metaliteracy and Transliteracy in the History Classroom: A Case Study Among Underserved Students - Cobourn, Alston; Brown, Jen Corrinne; Warga, Edward; Louis, Lisa (My University, 2022)
In the last twenty years, scholars have reimagined information literacy to better address an overly saturated world of information and the growing participatory culture of Web 2.0. Outside of library and information science (LIS), researchers have promoted transliteracy—the intersection between information, visual, digital, and other literacies—to help students find and assess information. Within the LIS discipline, metaliteracy has provided a foundation to rethink information literacy frameworks, redefining students as creators who produce and share information. Relatively few studies exist, however, on how to leverage literacies in support of student digital scholarship projects. Likewise, digital humanities professors promote metaliteracy in the classroom, yet fewer scholars create digital humanities projects or write case studies about them outside of research institutions, prestigious private colleges, and larger, well-established public history programs. This case study examines a class project for a small undergraduate Introduction to Public History course at Texas A&M University–Corpus Christi (TAMU–CC), a regional university with a comparatively large population of historically underserved students. Working with one archivist, two librarians, and the professor, students established a digital home for the ongoing South Texas Stories oral history project. Through this project, students learned and practiced various aspects of primary source literacy, information literacy, visual literacy, and digital literacy. The authors argue that such digital projects promote both metaliteracy and transliteracy, offering students a holistic learning experience during which they can practice their skills and that these types of projects are feasible at all kinds of institutions, even those with largely historically underserved populations.
Keywords: Archival literacy; Information literacy; Digital literacy; Metaliteracy; Transliteracy; Digital projects; Omeka; Public history; Hispanic Serving Institution; Underserved Students